Quand la lyrique des troubadours s’invite dans la narration - Anne Ibos-Augé (Revue des Langues Romanes)
Narrative occitan texts seem to have been less affected than their counterparts in the langue d'oïl by the phenomenon of lyrical insertions. However there are many procedures involving quotation, without having a real right to exist. Both registers - lyrical and narrative - are constantly shifting back and forth in the corpus of 13th- and 14th-century novas in the langue d'oc, and several procedures are encountered depending on the texts: the author's "dire", which explicitly quotes the “trouveur”, the anonymous song, which no longer quotes him, and the underlying intertext, a veritable "lyrical speech" borrowing from the songs’ repertoire. The study of these procedures will make it possible to question the reasons for and functions of the lyrical presence within occitan narrative textes.